New evidence for an association between the CSF HVA:5-HIAA ratio and psychopathic traits. Issue 7 (1st July 2003) - Soderstrom, H; Blennow, K; Sjodin, A-K; Forsman, A
Abstract : Objectives: To replicate the relation between the CSF HVA:5-HIAA ratio and psychopathic traits previously reported in a pilot group of 22 perpetrators of violent crimes. Methods: CSF monoamine metabolite concentrations in another 28 violent and sexual offenders, aged 45 or below, referred to pretrial forensic psychiatric investigation, were compared to features of psychopathy according to the Psychopathy Checklist–Revised (PCL-R). Results: Our previous finding was repeated in the new study group, where the HVA:5-HIAA ratio was strongly associated with psychopathic traits ( r = 0.50, p = 0.010), particularly its behavioural aspects ( r = 0.523, p = 0.004). In subsamples of individuals from both study groups who had no medication (n = 25) or no current axis I disorder, including a history of mood disorder or substance dependence (n = 21), the HVA:5-HIAA ratio remained strongly associated with all psychopathy factors but most closely with the behavioural features. Retrospective assessments of childhood disruptive symptomatology, such as attention deficit hyperactivity disorder or conduct disorder, analysed in relation to the monoamine metabolites, showed the same association with the HVA:5-HIAA ratio. Conclusions: Violent and aggressive behavioural traits with childhood onset and adult expression as psychopathic features are associated with changed activity in the brain dopaminergic system, possibly as a result of serotonergic dysregulation.